Knowledge and Attitude Toward Temporomandibular Disorders: A Survey in İstanbul - Tamer Celakil; Alp Saruhanoğlu (Galenos Yayinevi, 2022)
Objective: The aim of this study was to identify the strategies used for the diagnosis and treatment of patients with temporomandibular disorders (TMDs) by general dental practitioners (GDPs) in the city of Istanbul.Methods: A total of 154 GDPs were assessed by a single examiner in this questionnaire-based study. Descriptive statistics were calculated for all variables, and the results were analyzed at a 95% CI and statistical power of 80% with the significance level set at P < .05.Results:The most frequently employed strategies for obtaining a diagnosis were patients' medical history (33.1%), physical examination (37.7%), and a combination of diagnostic methods (29.2%). The most commonly referred specialties were prosthodontics (62.2%) and maxillofacial surgery (36.9%). All GDPs treated their TMD patients with occlusal splints, and the majority of the occlusal splints were hard occlusal splints (62.8%). Half of the GDPs considered the etiology of TMD to involve stress, whereas 49.4% believed that TMD is of a multifactorial etiology.Conclusion: The GDPs clarified that TMD patients were mostly treated with occlusal splints and this datum is consistent with the suggestions of previous consensus papers.